Syahailo Petro Trokhymovych To commemoration of a talented scientist is devoted (to 80-th birthday) - Department of pediatric surgery Department of pediatric surgery (Medičnì Perspektivi)
Syahailo Petro Trokhymovych To commemoration of a talented scientist is devoted (to 80-th birthday)